2018
DOI: 10.3116/16091833/19/3/179/2018
|View full text |Cite
|
Sign up to set email alerts
|

Optical encryption based on the algorithm of compressive ghost imaging and phase-shifting digital holography

Abstract: We present a compressive ghost-imaging encryption (GIE) scheme based on phase-shifting digital holography (PSDH). With our technique based on the PSDH, the optical information is recorded from each point of an object. Then each part of a hologram can reconstruct the original image, thus improving resolution of a reconstructed image. Using the characteristics of randomness of the PSDH, we improve security of the encryption scheme. In our simulations, a binary image is taken as a target and the mutual informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In recent years, CS-based optical encryption methods have been increasing the demand for many optical information processing applications [41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, CS-based optical encryption methods have been increasing the demand for many optical information processing applications [41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the intensity of the original object wavefield was decrypted from the reconstructed holograms by the inversion of PSDH process. Leihong et al [48] have experimentally presented compressive ghost imaging encryption based on PSDH. e simulation results have shown that the CS scheme improved the security and reconstruction quality of the intensity image.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation